FEMALE EFL LEARNERSâ REQUEST REALIZATION IN RELATION TO THEIR ETHNIC BACKGROUNDS - Artanti Puspita Sari (TEFLIN Journal: A publication on the teaching and learning of English, 2010)
Abstract: The choice of strategies and modifications of speech acts in conversational communication may be correlated with sociolinguistic factors, such as ethnicity, social distance and dominance. Requests, as a part of speech acts, provide an interesting focus in this research because requests are face threatening acts. This article was based on a research conducted in the period of April to June 2008. The subjects of the research were female EFL learners of English Education Study Program at Sriwijaya University Inderalaya in South Sumatera Indonesia. The investigation utilized a combination of qualitative and quantitative methods, revealed that: (1) in terms of patterns, the female EFL learners of different ethnic groups performed similar request patterns, (2) in terms of correlation, the subjectsâ ethnic backgrounds did not correlate with their strategies, yet, their ethnic backgrounds had correlation with the subjects request modifications, (3) the subjectsâ request strategies and modifications did not correlate with social distance and dominance. The information gained can be utilized as a basis for integrating cultures and social dimensions between speakers and hearers into the teaching of EFL as well as EIL to increase studentsâ intercultural and pragmatic competence.